(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Regarding the fundamental quality attributes of the communication process itself and its final result, the dependability and consistency of communication vary across a wide range of speech genres. The article’s major goal is to clarify and strengthen the evidentiary base for our hypotheses regarding the usual structural features of various speech genre formations in light of their dependability and consistency. The author makes an effort to show how the textual and cognitive mechanics of speech genres can be understood conceptually and hypothetically as universal anthropological variables of attention, engagement, and discovery. Due to the hazy boundaries between the aforementioned elements, the speech genre script’s three levels of reception are difficult to divide. Our in-depth analysis of the structure of speech genres in their naturally specific manifestations enables us to conclude that, in contrast to the cleanly reproduced speech genres in fiction, the proportion of truly flawless examples of dependability and consistency in everyday communication is not particularly high. When the communicator’s conception of their addressee or the assumed audience is understated, condescending, or twisted, low or noticeably weakened communication efficiency is very clearly shown.